Dimensi Partisi Graf Hasil Amalgamasi Siklus - Hasmawati Hasmawati; Ahmad Syukur Daming; Loeky Haryanto; Budi Nurwahyu (Jurnal Matematika, Statistika dan Komputasi, 2020)
Let be a connected graph G and -partition  of  end . The coordinat  to  is definition . If   for every two vertices in t , then  is a called  k-resolving partition of . The minimum k such that  is a k-resolving partition of  is the partition dimension of  and denoted by . In this paper, we show that the partition dimension for amlagamation of cycle graph  for To proof this results, we was used mathematical induction method.